Cytological Analysis of Root Cultures of Artemisia cina - Ermayanti, Tri Muji; Yanti, Oktavia; Hafiizh, Erwin Al (BRIN, 2004)
Artemisia cina is a medicinal plant species producing bioactive compounds which are potential a antitumor, antifungal and antibacterial. The aim of this study was to analyze the stability of chromosome number in root cultures of A. cina. Transformed root culture was established by infection of leaves of A. cina with Agrobacterium rhizogenes strains 07-20001, ATCC 15834, A4; and Agrobacterium tumefaciens strain R1000. Roots isolated from glasshouse plants, plantlets grown in solid and liquid MS medium were utilized for investigation of chromosome examination of untransformed roots. Chromosome examination was conducted by squashing method and chromosome numbers were calculated under microscope. The results showed that both untransformed and transformed root had in lability in the chromosome number, but had the modal number of chromosome x=8 with the diploid number of 2n =4x = 32. Roots isolated from glasshouse plants of A. cina had 53.7 of cell with the diploid numbers of 2n = 3 and 46.3% of cells had chromosome numbers ranged from 2n = 12 to 2n = 64. Untransformed roots isolated from plantlets cultured in solid medw had only 36.1% or cells with chromo orne number of 20 = 32, and untransformed roots grown in liquid medium had 49.4% of cells with 2n =32. The chromosome numbers of A. cina transformed roots was affected by trains of Agrobacterium. Root transformed with the bacterium Strain 07-20001 showed the highest in normal chromosome number of 2n = 32 (62.4%) followed by roots transformed with strains ATCC 15834 (61.9%). R1000 (43.6%) and A4 (43.0%). The range of the chromosome number of untransformed roots was from 2n=17 to 2n=64 whilst that of transformed roots was from 2n=11 to 2n=66.